Mondo Exotica : Sounds, Visions, Obsessions of the Cocktail Generation - Adinolfi, Francesco, 1960- (Book collections on Project MUSE., 2008)
Tiki torches, cocktails, la dolce vita, and the music that popularized them - Mondo Exotica offers a behind-the-scenes look at the sounds and obsessions of the Space Age and Cold War period as well as the renewed interest in them evident in contemporary music and design. The music journalist and radio host Francesco Adinolfi provides extraordinary detail about artists, songs, albums, and soundtracks, while also presenting an incisive analysis of the ethnic and cultural stereotypes embodied in exotica and related genres. In this encyclopedic account of films, books, TV programs, mixed drinks, and above all music, he balances a respect for exotica's artistic innovations with a critical assessment of what its popularity says about postwar society in the United States and Europe, and what its revival implies today.